Demographic factors and Financial Literacy among Individual Investors in Jaffna District, Sri Lanka - Prashanthan, V.; Balagobei, S. (International Conference on Business and Information - 2022, 2022)
The aim of the study is to examine the influence of demographic factors on financial literacy among individual investors in Jaffna district. Two hundred individual investors in Jaffna district were selected as sample by using random sampling technique and primary data was collected through a structured questionnaire. The financial literacy consists of three dimensions such as financial knowledge, financial behavior and financial attitude whereas gender, age, marital status, educational qualification, working experience, average monthly income and no of years involving in investment activities are considered as demographic factors. Data was analyzed using independent sample t-test and one-way ANOVA. The results reveal that there was no any significant difference in financial literacy between female and male. There is statistically significant difference in financial literacy among different age group of individual investors. But, there is no statistically significant difference in financial literacy among different marital status as well educational qualifications groups. Furthermore, it shows that there is a statistically significant difference in financial literacy among number of working experience of individual investors while there is a statistically significant difference in financial literacy among average monthly income groups as well as the number of years involving in investment activities. This research adds to the existing research that finds a number of demographic variables to be associated with financial literacy in a multivariate context.
Keywords: Demographic factors; Financial attitude; Financial behavior; Financial knowledge; Financial literacy